PERSEPSI MAHASISWA IAIN SURAKARTA TERHADAP RITUAL 1 SURO KERATON KASUNANAN SURAKARTA - Dian Puspa Safitri; Sohibussafa’ah Sohibussafa’ah; Arlin Dwi S (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to explain Kirab Malam 1 Suro, an annual event held by the Surakarta Sultanate Palace to commemorate the Islamic New Year. This research uses a phenomenological approach with qualitative research methods. The data is taken from the results of interviews and interviews conducted to determine the perception of Surakarta Isam Negeri Institute of Religion students on the Suro 1 ritual event at Kasunan Palace, which was represented by respondents from external campus Islamic student organizations. Kebo Bule is the king's favorite animal and as a symbol of safety in Kirab Malam 1 Suro. But on the other hand, a part of the Surakarta community as communica always has a great enthusiasm to join this event. Ordinary people believe that Kebo Bule is a buffalo magic, so they take the dirt from Kebo Bule Kyai Slamet who lined the road empty-handed. On the other hand, experts say that Kirab is used by the Keraton as a tool to communicate the existence and attractiveness of their tourism.Keyword: perception; Suro 1 night ritual; foreigners; external organizations; Kraton Kasunanan Surakarta.